1995
DOI: 10.2307/3236217
|View full text |Cite
|
Sign up to set email alerts
|

Influence of trees on above‐ground production dynamics of grasses in a humid savanna

Abstract: Abstract. Above‐ground grass biomass, necromass and tree litter were measured monthly over a vegetation cycle under tree clumps and in the open, in a humid savanna in Côte d'Ivoire. Grass production was calculated using several methods to better discriminate the contribution of the different grass compartments. Above‐ground grass biomass is higher in the open than under canopies during the second part of the growing season, but there is no difference in grass necromass dynamics. Physical protection of grass n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
2
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 20 publications
8
72
2
2
Order By: Relevance
“…This result agrees with other studies in semiarid environments which record that there is a higher density of the herbaceous component in open segments, where sunlight directly reaches the herbaceous stratum, facilitating recruitment (Crozier, & Boerner, 1984;Kessler, 1992;Belsky, 1994;Aguilera, & Lauenroth, 1995;Mordelet, & Menaut, 1995;Silva et al, 2008;Flores-Torres, & Montaña, 2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result agrees with other studies in semiarid environments which record that there is a higher density of the herbaceous component in open segments, where sunlight directly reaches the herbaceous stratum, facilitating recruitment (Crozier, & Boerner, 1984;Kessler, 1992;Belsky, 1994;Aguilera, & Lauenroth, 1995;Mordelet, & Menaut, 1995;Silva et al, 2008;Flores-Torres, & Montaña, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…The first model includes the herbaceous species that develop in more shaded locations, below the crown of woody plants; these are capable of inducing morphological changes in herbaceous species, so that they can increase the biomass produced (Kessler, 1992;Mordelet, & Menaut, 1995;Zhang, Wang, Liu, & Li, 2006;Legras et al, 2010). The second model encompasses the herbaceous species that thrive best in open areas (Crozier, & Boerner, 1984;Kessler, 1992;Belsky, 1994;Mordelet, & Menaut, 1995;Aguilera, & Lauenroth 1995;Silva et al, 2008). In this study, differences in the mean heights of plants between microhabitats confirmed the influence of establishment conditions on plant growth, showing that direct light is an important prerequisite for the development of the studied species.…”
Section: Discussionmentioning
confidence: 99%
“…light) when sheltered by shrubs in a shrub-dominant community. It is well known that shade has a significant influence on herbaceous growth, and woody plants may influence the environments under their canopies, changing SM and nutrients, light availability, and temperature (Belsky, 1994;Mordelet and Menaut, 1995;Scholes and Archer, 1997). Some studies have shown that understory sites have higher SM than open grassland sites (Joffre and Rambal, 1993;Scholes and Archer, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The selected tree clumps were made of three species, Bridelia ferruginea Benth., Crossopteryx febrifuga (Afzel. ex G. Don) Benth., Cussonia barteri Seeman and without any B. aethiopum (Mordelet and Menaut, 1995).…”
Section: Methodsmentioning
confidence: 99%